(3GdLQGFe GdeYdheGJjI (B/s - (3GdYQjGf, eMeO Ydjs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYI GdLOjOI(B, s, 2004)
(3LQGFe GdeYdheGJjI,XGgQI GdeYdheGJjI aj eLGd GdLQjeI,fXe GdMGSH GdBdj hGdeLQe GdeYdheGJj,GdCSGdjH GdZjQ eTQhYI aj GQJcGH GdLQjeI GdeYdheGJjI,GdJbfjGJ GdeSJNOeI aj JOejQ fXe GdeYdheGJjI,GdMeGjI GdLfGFjI dfXe GdeYdheGJjI,GdMeGjI GdLfGFjI ddHQGeL ef NdGd LQGFe GdCehGd,ChLg GdMeGjI GdeNJdaI dfXe GdeYdheGJjI aj CWhGQ GdbhGfjf GdNGUI,GdEJLGgGJ GdMOjKI aj GdMeGjI GdbGfhfjI dHQGeL GdMGSH GdBdj,GdMeGjI GdOhdjI dHQGeL GdMGSH GdBdj,GdMeGjI GdLfGFjI aj Xd GdbGfhf GdeUQj(B.s
(3HjHdjhZQGajG U(B.253s
Keywords: (3GdMhGSjHs; (3LQGFe GdeYdheGJjIs